Bank Saderat Iran : financial embezzlement under Sharia law - Oji, Chijioke (SAGE knowledge. Cases., 2016)
In September 2011, news of Bank Saderat Iran's involvement in an embezzlement operation became public. Amir Mansoor Khosravi, an Iranian businessman, had used fraudulent documents from Bank Saderat to obtain bank loans that amounted to 2.6 billion U.S. dollars. At the time, the fraud was the biggest in the history of Iranian banking and those implicated faced harsh penalties, including death sentences. As Iran's public prosecutor investigated the case, senior officials at Bank Saderat denied having any knowledge of the fraudulent operation.